Layanan Bimbingan Konseling Anak Usia 5-7 Tahun Bagi Korban Gempa Bumi Di Lombok Timur - Wadi, Hamzan; Wadi, Ardi Andika (Institut Agama Islam Negeri Padangsidimpuan, 2023)
Disasters always result in many changes, both material and non-material. And what is most worrying is children because they tend to have strong memories, so it can disturb the child's psychology. Therefore, this research will be focused To find out the treatment process through counseling services for children aged 5-7 years to overcome psychological problems for children affected by the earthquake. The forms of counseling guidance services provided to children who are experiencing trauma or psychological problems are orientation services, group counseling services, information services, individual counseling services, placement and distribution services, consultation, group guidance services, and mediation. This research is qualitative research. Finally, the author concludes that disorders that cannot be avoided by children are stress and trauma. And counseling guidance services are one solution to overcome trauma and stress as the right solution to overcome them.